2010
DOI: 10.3109/09513590.2010.495429
|View full text |Cite
|
Sign up to set email alerts
|

The expression of human leukocyte antigens class I and II in women with endometriosis or adenomyosis

Abstract: Women with endometriosis had a significantly higher expression of HLA molecules whereas in adenomyosis there was a tendency of lower expression of these molecules. This could explain the suppression of cellular immunity in the peritoneal cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…102 This uterine microenvironment is likely to significantly impact functionally relevant uNK cells in women with endometriosis. 71,105 Given that functioning uNK cells are vital for successful implantation and placentation, this change in activity may be key to endometriosis-associated infertility. However, resistance of eutopic endometrial cells to NK cell lysis may be an important factor as HLA class I expression is significantly higher in women with endometriosis compared to normal control subjects.…”
Section: Uterine Nk Cells Endometriosis and Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…102 This uterine microenvironment is likely to significantly impact functionally relevant uNK cells in women with endometriosis. 71,105 Given that functioning uNK cells are vital for successful implantation and placentation, this change in activity may be key to endometriosis-associated infertility. However, resistance of eutopic endometrial cells to NK cell lysis may be an important factor as HLA class I expression is significantly higher in women with endometriosis compared to normal control subjects.…”
Section: Uterine Nk Cells Endometriosis and Infertilitymentioning
confidence: 99%
“…However, resistance of eutopic endometrial cells to NK cell lysis may be an important factor as HLA class I expression is significantly higher in women with endometriosis compared to normal control subjects. 71,105 Given that functioning uNK cells are vital for successful implantation and placentation, this change in activity may be key to endometriosis-associated infertility. With such a clear role in successful fertility, it is surprising that so few studies have explored how uNK cells might explain the aetiology of endometriosis.…”
Section: Uterine Nk Cells Endometriosis and Infertilitymentioning
confidence: 99%
“…The MHC, also known as Human Leukocyte Antigens (HLA), are cell surface proteins that mediate interactions between immune responsive cells. Aberrant expression of both Class I and II MHC antigens in endometriotic lesions inhibits the cytotoxic activity of NK cells [143,144]. Some studies have suggested that the class I antigens HLA-B*07 and B*46 are associated with the development of endometriosis, whereas HLA-B*48 may offer a protective effect [145,146].…”
Section: Introductionmentioning
confidence: 99%
“…The MHC, also known as Human Leukocyte Antigens (HLA), are cell-surface proteins that mediate interactions between immune responsive cells. Aberrant expression of both Class I and II MHC antigens in endometriotic lesions inhibits the cytotoxic activity of natural killer cells (NK) (73,74). Some studies have suggested that the class I antigens HLA-B*07 and B*46 are associated with the development of endometriosis, whereas HLA-B*48 may offer a protective effect (75,76).…”
Section: Cellular Mechanismsmentioning
confidence: 99%